Implementation of the Independent Curriculum in Improving the Quality of Education in SMA Negri 1 Belitang III - Permatasari, Pinky; Aldi, Khoirul; Nidiatika, Anggun; Maja, Gergely (Scientechno: Journal of Science and Technology, 2023)
The curriculum is the "spirit" of education that must be innovative, dynamic, and periodic in accordance with the times and science and technology, competencies needed by society and graduate users. The curriculum is seen as objectives, contexts and strategies in learning through programs of developing learning instruments or materials, social interaction and systematic learning techniques in educational institutions. Curriculum changes to ensure the learning process in schools/madrasahs is better. Curriculum changes – thus – are a must. The Ministry of Education, Culture, Research, and Technology (Kemendikburistek) issued a policy in the development of the Independent Curriculum which is given to education units as an additional option in order to restore learning during 2022-2024 and improve the quality of education. Therefore, this article explains the Implementation of the Independent Curriculum in improving the Quality of Education implemented at SMA NEGERI 1 BELITANG III. This study used a qualitative approach, in collecting data using participatory observation, study documentation, and interviews. In this study, there are 3 aspects in the implementation of the independent curriculum, namely planning the implementation of the independent curriculum, implementing the independent curriculum and evaluating the Independent Curriculum Learning. The purpose of the research in this article is to determine the impact of the implementation of the independent curriculum in improving the quality of education at SMA Negeri 1 Belitang III.